The Effectiveness of School Operational Assistance (BOS) Fund Management in Developing Teacher Professionalism at SMP Swasta Raudhatul Jannah, Subulussalam City - Riswan Berutu; Candra Wijaya; Muhammad Rifa'i (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The activity of allocating funds for the operational implementation of education is a very complex activity. Therefore, education financing is very important and crucial. The purpose of this study is to determine the budget planning, implementation, supervision, and accountability of BOS funds in order to determine whether the management of BOS funds is effective and can develop teacher professionalism at Raudhatul Jannah Private Junior High School, Subulussalam City. This study uses a qualitative approach with a qualitative descriptive approach. The results of the study indicate that: 1) BOS fund planning is carried out through the formation of a management team and consultation with school stakeholders; 2) the use of BOS funds is in accordance with Permendikbud No. 63 of 2023; 3) supervision is carried out by ensuring budget compliance with JUKNIS; and 4) overall, BOS funds effectively support the development of teacher professionalism in improving the quality of education.